Development of CW and pulsed thulium ytterbium co-doped fiber lasers using nano-engineered yttria-alimina-silica based gain medium in conjunction with cladding pumping technique - Harun, Sulaiman Wadi; Shamsudin, H.; Ahmad, Harith; Halder, A.; Paul, M.C.; Pal, M.; Bhadra, S.K. (Bentham Science Publishers, 2016)
Background: Pulsed fiber lasers operating near 1900 nm are becoming emerging laser sources for scientific and industrial applications, because of their unique advantages in terms of eye-safe wavelength, and high absorption in greenhouse gases, liquid water, and most polycarbonate materials. We develop new nanoengineering double-clad Thulium-Ytterbium co-doped fiber (TYDF) to provide an efficient lasing at 1950 nm region based on energy transfer from Ytterbium to Thulium ion. The performance of the TYDF is investigated for both continuous wave (CW) and pulse laser operations. Methods: The TYDF is fabricated using a Modified Chemical Vapor Deposition (MCVD) process in conjunction with solution doping technique. The lasing characteristic of the TYDF laser (TYDFL) is investigated for both linear and ring configurations. The pulse generations are demonstrated using various passive saturable absorbers (SAs) such multiwalled carbon nanotubes (MWCNTs) and graphene oxide. Results: With a linear configuration, the TYDFL operates at center wavelength of 1936.4 nm, 1958.6 nm and 1967.5 nm at gain medium lengths of 5 m, 10 m and 15 m, respectively. The proposed laser produces the highest efficiency of 9 .9 % at 10 m long TYDF and the lowest threshold pump power of 400 mW at a longer TYDF length of 15 m. The Q-switched laser operates at 1960 nm region is achieved by exploiting a MWCNTs embedded in polymer composite film as a SA. The proposed TYDFL generates a stable pulse train with repetition rates and pulse widths ranging from 18.9 to 35.1 kHz and 7.94 to 1.52 μs, respectively by varying the multimode 980 nm pump power from 440 mW to 528 mW. The maximum pulse energy of 11.2 nJ is obtained at the pump power of 512 mW. A higher performance Q switching is expected to be achieved with the optimization of the laser cavity and SA. A mode-locked TYDFL is also demonstrated using a graphene oxide (GO) based SA. The laser operates at 1942.0 nm with a threshold pump power as low as 1.8 W, a repetition rate of 22.32 MHz and calculated pulse duration of 1.1 ns. Conclusion: The developed TYDF is capable for use in developing both CW and pulsed fiber laser in conjunction with cladding pumping technique.